Study Tentang Konsentrasi Pegawai FTM BerdasarkanSuhu, Body Mass Index, Lama Pemakaian Masker, dan UsiaMenggunakan Fasilitas Ruang Iklim - Hermita Dyah Puspita; Norina, Rida; Budi Astuti (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2024)
COVID-19 has spread rapidly in places where people interact socially, with aerosol transmission being a significant concern, especially in enclosed spaces where infected individuals spend extended periods with others in crowded and poorly ventilated conditions. The use of masks is a preventive measure against the spread of the virus that causes COVID-19. Concerns have been raised that carbon dioxide may accumulate in masks over time, potentially leading to respiratory issues and other problems such as impaired concentration at work. This research aims to conduct an experiment to study concentration based on the physical work environment, including factors such as room temperature, Body Mass Index (BMI), duration of mask use, and age. Concentration will be measured through reaction time, which includes visual, auditory, and motor components, using a factorial design method. The results of the study indicate a significant relationship between the concentration, represented by the reaction time of the respondents, and several factors: temperature, BMI, age of the respondents, and type of reaction (visual, auditory, and motor). Based on factorial analysis, it can be concluded that temperature, age, BMI, and type of reaction all influence reaction time at a significance level of 5%.